2022
DOI: 10.1186/s11658-022-00379-9
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic overexpression of miR-92a-2-5p ameliorated cardiomyocyte oxidative stress injury in the development of diabetic cardiomyopathy

Abstract: Background Diabetic cardiomyopathy (DCM) results from pathological changes in cardiac structure and function caused by diabetes. Excessive oxidative stress is an important feature of DCM pathogenesis. MicroRNAs (miRNAs) are key regulators of oxidative stress in the cardiovascular system. In the present study, we screened for the expression of oxidative stress-responsive miRNAs in the development of DCM. Furthermore, we aimed to explore the mechanism and therapeutic potential of miR-92a-2-5p in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In a type 2 diabetic rat model, the overexpression of miR-92a-2-5p attenuated oxidative stress. 69 Additionally, transfecting human endothelial progenitor cells from myocardial infarction patients and healthy controls with a miR-324-5p mimic resulted in a significant reduction in ROS levels. 70 miR-181c targets mitochondrial function by altering the expression of mitochondrial genes, such as mt-COX1, a subunit of complex IV of the respiratory chain, leading to increased ROS production.…”
Section: Overview Of Potential Mechanisms Of Cardiotoxicity Associate...mentioning
confidence: 99%
“…In a type 2 diabetic rat model, the overexpression of miR-92a-2-5p attenuated oxidative stress. 69 Additionally, transfecting human endothelial progenitor cells from myocardial infarction patients and healthy controls with a miR-324-5p mimic resulted in a significant reduction in ROS levels. 70 miR-181c targets mitochondrial function by altering the expression of mitochondrial genes, such as mt-COX1, a subunit of complex IV of the respiratory chain, leading to increased ROS production.…”
Section: Overview Of Potential Mechanisms Of Cardiotoxicity Associate...mentioning
confidence: 99%
“…For instance, Zhu et al indicated that overexpression of miR-340-5p [ 59 ] in cardiomyocytes led to increased mitochondrial functional loss, oxidative stress, and cardiomyocyte apoptosis in diabetic mice by targeting myeloid cell leukemia 1(Mcl-1). Yu et al [ 60 ] observed that decreased miR-92a-2-5p expression was also detected in high glucose-induced cardiomyocytes. Overexpression of miR-92a-2-5p ameliorated cardiomyocyte oxidative stress injury, by inhibiting MKNK2 expression and leading to decreased phosphorylation of p38-mitogen-activated protein kinase(MAPK) signaling.…”
Section: Micrornasmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of small non-coding RNAs that play essential roles in diverse biological processes. As crucial epigenetic modulators, miRNAs can regulate the expression of target genes by binding to 3′ untranslated region (3’ UTR) without sequence alteration [ 15 , 16 ]. The miR-17-92 cluster is a highly conserved miRNA cluster containing six members (miR-17, miR-18a, miR-19a, miR-19b-1, miR-20a, and miR-92a-1) that collectively participate in a variety of physiological and pathological processes [ 17 ].…”
Section: Introductionmentioning
confidence: 99%